Combining photoredox and silver catalysis for azidotrifluoromethoxylation of styrenes. Issue 35 (16th April 2018) - Cong, Fei; Wei, Yongliang; Tang, Pingping
Abstract : An intermolecular azidotrifluoromethoxylation of styrenes by synergistic visible-light-mediated photoredox and silver catalysis has been reported for the first time. Abstract : The first example of an azidotrifluoromethoxylation of styrenes has been achieved by synergistic visible-light-mediated photoredox and silver catalysis. Trifluoromethyl arylsulfonate (TFMS) and the Zhdankin reagent were used as the trifluoromethoxylation reagent and the azide source, respectively. A good functional group tolerance and mild reaction conditions of this method are applicable to late-stage azidotrifluoromethoxylation of complex small molecules. Furthermore, the mechanistic investigations indicate the single-electron transfer involved in the reaction.